Patentability and Knowledge Spillovers of Basic R&D. (1st April 2013) - Chu, Angus C.; Furukawa, Yuichi
Abstract : This study develops a research and development (R&D)–based growth model with basic and applied research to analyze the growth and welfare effects of two patent instruments: (i) the patentability of basic R&D and (ii) the division of profit between basic and applied researchers. We find that for the purpose of stimulating basic R&D and economic growth simultaneously, increasing the share of profit assigned to basic researchers is more effective than raising the patentability of basic R&D, which has either a negative effect or an inverted‐U effect on technological progress. However, a benevolent patent authority requires both patent instruments to achieve the socially optimal allocation in the decentralized economy.